Analisis Undang-Undang Nomor 41 Tahun 2004 dan Hukum Islam tentang Wakaf terhadap Tugas Nazhir pada Aset Wakaf Masjid Al-Huda Kabupaten Sumedang - Aditya Yunianto; Siska Lis Sulistiani; Asep Ramdan Hidayat (UNISBA Press, 2024)
Abstract. Al-Huda Mosque has not been administered in legal legality. This is due to several factors, including Nazhir as the waqf manager who was given a mandate by the Wakif has not carried out all his duties and obligations properly, resulting in problems with the sale and purchase of waqf assets. This is in conflict with Law Number 41 of 2004 Article 40 that waqf assets, among others, may not be traded and Islamic Law which has implications in Article 11 concerning the duties of nazhir. Based on this phenomenon, the problems in this study are formulated (1) How is the analysis of Law Number 41 of 2004 concerning Waqf regarding the duties of nazhir on the waqf assets of the Al-Huda Mosque in Sumedang Regency (2) How is the analysis of Islamic Law regarding the duties of nazhir on the waqf assets of the Al-Huda Mosque in Sumedang Regency. This study is a normative legal research conducted at the Al-Huda Mosque, North Sumedang District, Sumedang Regency, using qualitative research. The research approach uses a normative legal approach. There are two sources of research data used, namely: data source The results of this study are that nazhir in carrying out his duties does not fulfill his duties. Reviewed from Law Number 41 of 2004 Article 11 Nazhir only manages waqf assets and reviewed from Islamic law, the rules of fiqh which means